Student attendance system using QR code - Ahmad Qusyairi, Ahmad Kamarulzaman (2019)
Smartphones are one of most important item that almost everyone own, especially for university students. The number of new students that entering university are increasing every year. Thus, it will become difficult for every lecturer to handle the student attendances. Student Attendance System Using QR Code (SASYS) is proposed to help lecturer to collect the student’s attendance in a systematic way. This system was developed due to the a few problems being encountered by the university lecturer such as they need update their student’s attendance during the class session. Lecturer have two choices whether called their student’s name one by one or just giving an attendance sheet. Apart from that, this causes a lot of waste and it always will be required some cost. Sometimes, students also experience that their attendance did not enter the system. However, all of the above problem since this system able to detect the QR codes. This system also can store data into the database and generate reports. The expected outcome is that the lecturer job can be done easier rather than making mistakes.